Oro-pharyngeal carriage and antimicrobial susceptibility of streptococcus pneumoniae from healthy children - Rashid Z.Z.; Isahak I.; Chiam P.J.; Suki M.H.; Mohamad N.A.; Hussain D.; Sim T.Y.; Jaafar H.M.; Yusof Y.A.M.; Rahman M.M. (2024)
Indexed by Scopus